Deprivasi Tidur dan Implikasinya terhadap Disregulasi Mahasiswa Semester 5 Tasawuf dan Psikoterapi - Sri Andani Zajijilah (HARAPAN: Jurnal Ilmu Kesehatan dan Psikologi, 2026)
Sleep deprivation is a prevalent issue among university students and has become an increasingly significant concern due to its adverse effects on emotional well-being and academic performance. Fifth-semester students, who generally face intensive coursework, research assignments, and organizational responsibilities, are particularly vulnerable to insufficient sleep. This study aims to analyze the implications of sleep deprivation on the dynamics of emotional regulation among students in the Sufism and Psychotherapy Program by employing a qualitative case study approach. Data were collected through in-depth interviews, non-participant observations, and documentation involving selected participants who experienced recurring sleep deprivation during the academic semester. The data were analyzed using thematic analysis to identify patterns of emotional responses, coping strategies, and perceived academic consequences. The findings reveal that sleep deprivation substantially reduces students' ability to regulate emotions, leading to heightened emotional reactivity, irritability, anxiety, and difficulty managing academic pressure. Participants also reported diminished concentration, impaired reflective thinking, decreased motivation, and challenges in maintaining constructive interpersonal relationships with peers and lecturers. Despite employing various coping mechanisms rooted in spiritual reflection and emotional self-awareness, these strategies were often insufficient to offset the cumulative effects of chronic sleep loss. The study demonstrates that adequate sleep is not merely a physiological necessity but also a critical determinant of emotional resilience, cognitive functioning, and academic engagement. These findings highlight the importance of promoting healthy sleep habits and psychological support programs within higher education institutions to enhance students' emotional regulation, well-being, and overall academic success.